Intermediate Monocytes and Cytokine Production Associated With Severe Forms of Chagas Disease - Gómez-Olarte, Sergio; Bolaños, Natalia I.; Echeverry, Mariana; Rodríguez, Ayda N.; Cuéllar, Adriana; Puerta, Concepción J.; Mariño, Alejandro; González, John M. (Frontiers in Immunology, 2019)
Monocytes are classified according to their CD14 and CD16 expression into classical (reparative), intermediate (inflammatory), and non-classical. This study assessed the frequency of monocyte and the relationship between monocyte subset percentages and the levels of blood cytokines in Colombian chagasic patients with different clinical forms. This study included chagasic patients in different clinical stages: indeterminate (IND) n = 14, chronic chagasic cardiomyopathy (CCC) n = 14, and heart transplant chagasic (HTCC) n = 9; controls with non-chagasic cardiopathy (NCC) n = 15, and healthy individuals (HI) n = 15. Peripheral blood mononuclear cells (PBMCs) were isolated, labeled for CD14, CD16, and HLA-DR, and analyzed by flow cytometry. Cytokines were measured with a bead-based immunoassay. Percentages of total CD14+ CD16+ and CD14+ HLA-DR+ monocytes were higher in patients with heart involvement (CCC, HTCC, and NCC) than controls. Percentages of intermediate monocytes increased in symptomatic chagasic patients (CCC and HTCC) compared to asymptomatic chagasic patients (IND) and controls (HI). Asymptomatic chagasic patients (IND) had higher percentages of classical monocytes, an increased production of CCL17 chemokine compared to chagasic symptomatic patients (CCC), and their levels of CCL17 was positively correlated with the percentage of classical monocyte subset. In CCC, the percentages of intermediate and classical monocytes were positively correlated with IL-6 levels, which were higher in this group compared to HI, and negatively with IL-12p40 concentration, respectively. Remarkably, there also was an important increased of classical monocytes frequency in three chronic chagasic patients who underwent cardiac transplant, of which one received anti-parasitic treatment. Our findings suggest that cardiac chagasic patients have an increased percentage of inflammatory monocytes and produce more IL-6, a biomarker of heart failure and left ventricular dysfunction, whereas asymptomatic chagasic individuals present a higher percentage of reparative monocytes and CCL17.